Phenomenological modeling of the suprathermal electron generation during magnetic field line reconnections in Experimental Advanced Superconducting Tokamak - Marchuk, Yu.M.; Pankratov, I.M. (Вопросы атомной науки и техники, 2017)
The strong suprathermal electron generation is modeled in conditions of bursts of the strong MHD plasma activity in the Experimental Advanced Superconducting Tokamak (EAST) when magnetic field line reconnections took place. Because of the fast changes in the magnetic flux during these magnetic field line reconnections the instant bursts of the induced electric field occur. The instant changes in suprathermal electron density during these bursts of the induced electric field have been analyzed.